Pengaruh Rasio Keuangan terhadap Perubahan Laba pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2023 - Mira Listiani; Eko Adi Widyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this research is to determine and analyze the influence of the current ratio, debt to asset ratio, and return on asset both partially and simultaneously on profit changes in pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2018-2023. This research is of a descriptive quantitative type, using purposive sampling method for data collection. The data used are secondary data taken from the financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2018-2023. The results of this study indicate that the coefficient of determination (R2) value is 0.762, which shows that the contribution of the current ratio, debt to asset ratio, and return on asset variables to profit changes is 76.2%. Meanwhile, the remaining 23.8% is influenced by other factors not included in this study. The results of the hypothesis test show that the current ratio partially does not affect profit changes. Meanwhile, the debt to asset ratio and return on asset partially affect profit changes. Simultaneously, the current ratio, debt to asset ratio, and return on asset affect profit changes in pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2018-2023.